THE STYLISTIC ROLE OF DETERMINOLOGISMS IN THE COMPOSITION OF COMPARISONS (based on Bohdan Lepky`s story “Motrya”) - Zoriana J. Kunch. (Вісник університету ім. А. Нобеля. Серія Філологічні науки, 2023)
The article analyzes the use of determinologisms in the comparisons composition as a feature of the writer`s creative manner based on Bohdan Lepky`s story “Motrya”. In order to find out the stylistic role and methods of achieving an artistic effect with the help of this trope, we have implemented several tasks: to carry out a continuous selection of comparisons using determinologisms from B. Lepky`s historical story “Motrya”; to analyze the selected comparisons concerning the formal way of achieving comparability and identify which of them are typical for the writer`s style; to outline the thematic categories of determinologisms used in comparisons; to find out the stylistic possibilities of comparisons with the use of determinologisms in an artistic work; to describe the characteristic features of B. Lepky`s creative style related to the use of comparisons. In our research, we have used the following methodology: the method of continuous selection was used to select quotes from the novel`s text in which the author used comparisons of different types, including determinologisms, also with the help of structural-thematic and semantic analysis, the selected comparisons were classified according to the formal ways of achieving comparability. Statistical methods made it possible to identify the quantitative parameters of the studied material. Descriptive, comparative, component, and deductive research methods were also used to realize the set goal. Based on the analysis of 167 quotes selected from the text of B. Lepky`s story “Motrya”, the author used a comparison with the involvement of determinologisms, direct comparison (comparative phrase, subordinate comparative clause), indirect comparison, and logical comparison. There is a significant quantitative advantage of direct comparisons (63 %). To create direct comparisons, the writer uses more often the conjunction “як” (70,2 %), less often “ніби” (16.7 %), and other comparative conjunctions occur sporadically. An essential feature of the writer`s creative manner is the predominance of complex abstract concepts comparisons with simple, understandable determinologisms of several thematic groups for every reader. The largest groups are zoological and technical determinologisms relating to various craft professions, military, artistic, geographical, climatic, astronomical determinologisms, and others. We observe that determinologisms are not perceived in the artistic text as something foreign. They reflect the peculiarities of the modern author`s communicative space, testify to his high intellectual level, and are directed to the same educated readers. A comparison is a vivid means of expressing the author`s attitude towards a particular person or phenomenon since there is no real connection between the compared and the comparative object, and the writer chooses the object of comparison with his creative imagination and determines the comparative feature. That all contributes to the emergence of a particular expression. In B. Lepky`s story “Motrya”, the stylistic role of comparisons manifests itself: it focuses attention on some feature of an object or phenomenon by comparing it with another object or phenomenon where this feature stands out very clearly. The analyzed material found comparisons based on attributive, adjectival, or predicative features. We have established that the comparison through the juxtaposition of language units from different thematic fields emphasizes the content and creates a unique artistic effect: significant semantic features are actualized, additional connotations are superimposed, and an original image appears, which makes a particular expressive impression on the readers. The following characteristic features of B. Lepky`s creative manner, related to the use of comparisons, which include determinism, have been identified: the dominance of the conjunction as in direct comparisons; the prevalence in comparisons of well-known zoological and technical determinologisms, which expand their semantic field and contribute to the emotionality of the expression; the highly specialized determinologisms revealed in the analyzed material are organically included in the artistic context and become an essential component of the writer`s individual authorial style; logical comparisons are usually accompanied by the author`s reasons explanation for the comparison, thus creating a kind of author`s extended allegory combined with the comparison; comparisons are often combined with other stylistic devices (rhetorical appeal, allegory, irony, metaphor, parallelism, etc.); the writer demonstrates his commitment to folk Ukrainian traditions, the use of comparisons involve folk proverbs, sayings, unfavorable comparisons, etc.